The Relationship Between Social Support and Academic Resilience In First-Year Migrant Students at Universitas Negeri Makassar - Sari, Dewita; Razak, Ahmad; Jalal, Novita Maulidya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to determine the relationship between social support and academic resilience in first year migrant students at Universitas Negeri Makassar. The respondents in this research were 125 first year students at Negeri Makassar who had migrated. Data collection was carried out using the academic resilience scale and social support scale. Hypothesis testing used Spearman Rho correlation analysis with the help of SPSS 25. The results showed that there was a relationship between social support and academic resilience in first year migrant students at Universitas Negeri Makassar with a significance value of 0.00 < 0.05. This means that the higher the social support, the higher the academic resilience of first year students.